Net Assimilation Rate and Agronomic Efficiency of Nitrogen in Tartago (Ricinus communis L.) (Euphorbiaceae) in Dry Climate - Ernesto Díaz-López; Jesús M. E. Aguilar-Luna; Juan M. Loeza-Corte (Scientifica)
To know the dynamics of net assimilation rate and the agronomic efficiency of nitrogen in the Tartago crop, seeds of three accessions were collected in Teotitlán de Flores Magón, Oaxaca, Mexico. The treatments consisted of nitrogen fertilization of 0, 20, 40, 60, 80, 100, 120, and 140 kg (N) ha−1, evaluated under a completely randomized design. The experimental unit was constituted by a Tartago plant inside of a polyethylene bag with soil of the zone, and four repetitions were considered. The response variables were dry biomass, number of fruits per plant, agronomic yield, harvest index, nitrogen agronomic efficiency, SPAD units, and net assimilation rate. The results indicate that climatic conditions did not influence the growth and development of the crop. The maximum values for all of response variables were achieved with the application of nitrogen in a range of 60 to 140 kg ha−1. The net assimilation rate was adjusted to a quadratic model. It is concluded that the Tartago responds positively to the application of nitrogen and can be an alternative to be grown in dry climate.